Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.12688/f1000research.27868.3
|View full text |Cite
|
Sign up to set email alerts
|

WIND (Workflow for pIRNAs aNd beyonD): a strategy for in-depth analysis of small RNA-seq data

Abstract: Current bioinformatics workflows for PIWI-interacting RNA (piRNA) analysis focus primarily on germline-derived piRNAs and piRNA-clusters. Frequently, they suffer from outdated piRNA databases, questionable quantification methods, and lack of reproducibility. Often, pipelines specific to miRNA analysis are used for the piRNA research in silico. Furthermore, the absence of a well-established database for piRNA annotation, as for miRNA, leads to uniformity issues between studies and generates confusion for data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…These need to be further verified by bioinformatics tools or experimental verification. Moreover, these lines of new evidence may also counsel us to pay more attention to future research on circulating piRNAs, and targeting piRNAs cannot be identified by simply mapping small RNA-seq data to piRNA databases ( Geles et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These need to be further verified by bioinformatics tools or experimental verification. Moreover, these lines of new evidence may also counsel us to pay more attention to future research on circulating piRNAs, and targeting piRNAs cannot be identified by simply mapping small RNA-seq data to piRNA databases ( Geles et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the principles detailed in the WiND workflow [ 21 ], the RNA sequencing data were analyzed for piRNA and other sncRNAs. RNASeq was aligned to the GRCh38 genome using STAR, followed by FeatureCounts from the Rsubread package, and, simultaneously, de Novo transcriptome counts with Salmon.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of sncRNAs was assessed using WIND (Workflow for PIRNAs and Beyond D) [ 21 ], a bioinformatics workflow that addresses the crucial issue of small RNA annotation, allowing for reliable identification of piRNAs and other sncRNAs that have been misclassified as piRNAs in the past.…”
Section: Methodsmentioning
confidence: 99%
“…miRanda [ 17 ], pirnaPre [ 67 ], and pirScan [ 18 ] have been used for piRNA target prediction, and three algorithms have been proposed for predicting piRNA clusters from sRNA-seq data: proTRAC [ 54 ], piClust [ 68 ], and PILFER [ 69 ]. In addition, multiple integrated platforms, such as sRNAtools [ 70 ] and Workflow for piRNAs and Beyond (WIND) [ 71 ], have been recently developed for piRNA annotation and downstream analysis from raw data to plots and statistics by sRNA-seq. The performances of most of these piRNA prediction tools have been reviewed by Liu et al [ 46 ].…”
Section: Identification Of Pirnamentioning
confidence: 99%